2014
DOI: 10.12740/pp/24452
|View full text |Cite
|
Sign up to set email alerts
|

The sense of coherence in women undergoing coronary arteriography

Abstract: CelCelem pracy była ocena poczucia koherencji w grupie kobiet poddanych diagnostyce inwazyjnej choroby wieńcowej i próba powiązania siły poczucia koherencji z krytycznymi przewężeniami tętnic wieńcowych.MetodaDo oceny poczucia koherencji użyto Kwestionariusz Orientacji Życiowej SOC-29 Antonovsky’ego oraz specjalnie skonstruowany kwestionariusz zawierający dane socjodemograficzne. Badania prowadzono przed i po 6-9 miesiącach od badania koronarograficznego. Wynik badania angiograficznego decydował o zakwalifiko… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 14 publications
1
9
0
Order By: Relevance
“…Stemming from that study, women with cardiac syndrome X appeared to experience a higher level of anxiety several months after coronary angiography compared to women with diagnosed significant atherosclerosis in coronary vessels [4]. There were no statistically significant differences in the estimation of depressive symptoms in both groups [5]. Moreover, women with no significant stenosis of coronary arteries demonstrated a lower sense of comprehensibility before and after coronarography and lowered manageability after the procedure [6].…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…Stemming from that study, women with cardiac syndrome X appeared to experience a higher level of anxiety several months after coronary angiography compared to women with diagnosed significant atherosclerosis in coronary vessels [4]. There were no statistically significant differences in the estimation of depressive symptoms in both groups [5]. Moreover, women with no significant stenosis of coronary arteries demonstrated a lower sense of comprehensibility before and after coronarography and lowered manageability after the procedure [6].…”
Section: Introductionmentioning
confidence: 84%
“…Depressive and anxiety disorders often accompany cardiovascular disease. Most data are available on ischemic heart disease and heart failure [1][2][3][4][5][6]. Relatively little information is available on the symptoms of depression and anxiety in patients with carotid atherosclerosis and their relationship with the sense of coherence (SOC) [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Individual researchers were set the cut-off points themselves ( 17 ). Some studies suggest that reaching around 140–160 points indicates a strong, 110–130-a moderate, and below 100–a low SOC level ( 5 , 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a high SOC is related to a better quality of life, better health perception, or better adaptation to the disease. Furthermore, other studies have reported that SOC could be an indicator of psychological well-being, identifying a possible relationship with anxiety and depression [ 8 , 46 , 51 , 70 ]. In particular, a high SOC is related to low levels of anxiety and depression.…”
Section: Introductionmentioning
confidence: 99%